Recent Updates on Experience, Treatment and Prevalence of Adult Brain Tumor : Single Center Study - Tommy Rizky Hutagalung; Ridha Dharmajaya (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Introduction : Brain tumor is a disease with high morbidity and mortality rates. Treating brain tumors requiring medical providers to have basic understanding of brain tumor diagnosis and management. The most common brain tumors are meningiomas, gliomas, pituitary adenomas and brain metastasis. The treatment of each type of brain tumor is different and multidisciplinary involving other scientific fields besides neurosurgery. Case Series : We reported 131 cases of brain tumors at the Haji Adam Malik Hospital in the period January 2018-December 2019, consisting of 52 cases (40%) of meningioma, 34 cases (26%) of Glioma , 12 cases (9%) of pituitary adenomas and 33 cases (25%) of brain metastasis. Meningiomas were mostly treated with surgery alone in 38% of cases, gliomas with surgery followed by chemo-radiation in 41% of cases, all of pituitary adenomas were treated with endonasal transfenoid surgery, while brain metastasis in 70% of cases required whole brain radiation with controlled primary tumors. Discussion : The modalities for treating brain tumor patients has been increasing recently. Meningiomas are mostly benign and managed by surgical resection only, chemo-radiation reserved for high risk or refractory case of meningiomas. Glioblastoma is the most common glioma and aggressive malignant primary brain tumor, limited response to gross surgical tumor and chemo-radiation. Pituitary adenomas mostly treated with endonasal transfenoid surgery, radiotherapy use in recurrent case. Brain metastasis may require complex multidisciplinary care with neurosurgery, radiation oncology, and medical oncology. Conclusion: The treatment of brain tumors is influenced by various considerations such as age, patient condition,neurological deficits, location of the tumor, comorbidities, experience of the neurosurgeon and available modalities. Treatment methods for brain tumors continue to evolve.